Commercial bank credit policy - Ponomarenko, Julia; Trygub, Inna (My University, 2014)
The proper organization of the process of bank lending, the development of efficient and flexible management of credit operations are the basis of financial stability and market stability of commercial banks. Commercial bank credit policy outlines the range of key goals and objectives of banking, sets out specific techniques, methods and techniques for its implementation and has a significant impact on the economic development of the country as a whole. Правильна організація процесу банківського кредитування, розробка ефективного та гнучкого управління кредитними операціями є основою фінансової стабільності та ринкової стабільності комерційних банків. Кредитна політика комерційних банків окреслює коло ключових цілей та завдань банківської справи, визначає конкретні прийоми, методи та методи її реалізації та має значний вплив на економічний розвиток країни в цілому.
Keywords: credit policy; banking system; банківська система; кредитна політика; кафедра ділової іноземної мови та міжнародної комунікації